2019
DOI: 10.4171/rmi/1103
|View full text |Cite
|
Sign up to set email alerts
|

Upper bounds for the spectral function on homogeneous spaces via volume growth

Abstract: We use spectral embeddings to give upper bounds on the spectral function of the Laplace-Beltrami operator on homogeneous spaces in terms of the volume growth of balls. In the case of compact manifolds, our bounds extend the 1980 lower bound of Peter Li [17] for the smallest positive eigenvalue to all eigenvalues. We also improve Li's bound itself. Our bounds translate to explicit upper bounds on the heat kernel for both compact and noncompact homogeneous spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…As mentioned earlier, the lower bound was proved in [34]. (An improved lower bound was recently obtained in [28].) To obtain an upper bound, we note that…”
Section: The Poincaré Inequality On Compact Lie Groupsmentioning
confidence: 92%
See 2 more Smart Citations
“…As mentioned earlier, the lower bound was proved in [34]. (An improved lower bound was recently obtained in [28].) To obtain an upper bound, we note that…”
Section: The Poincaré Inequality On Compact Lie Groupsmentioning
confidence: 92%
“…When (M, g) is a compact homogeneous space, C. Judge and R. Lyons in [28] have recently obtained the following uniform upper bound.…”
Section: The Poincaré Inequality On Compact Lie Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Judge and Lyons [JL19] improved it. Recall that a Riemannian manifold is called homogeneous if its isometry group acts transitively on it.…”
Section: Introductionmentioning
confidence: 99%
“…During the review process, the author found the recent article by Judge and Lyons, which improves the lower bound in .…”
mentioning
confidence: 99%